2017
DOI: 10.7554/elife.23785
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activation of kappa opioid receptors at ventral tegmental area inhibitory synapses following acute stress

Abstract: Stressful experiences potently activate kappa opioid receptors (κORs). κORs in the ventral tegmental area regulate multiple aspects of dopaminergic and non-dopaminergic cell function. Here we show that at GABAergic synapses on rat VTA dopamine neurons, a single exposure to a brief cold-water swim stress induces prolonged activation of κORs. This is mediated by activation of the receptor during the stressor followed by a persistent, ligand-independent constitutive activation of the κOR itself. This lasting chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 84 publications
2
25
1
1
Order By: Relevance
“…Given the role of dynorphin/KOR interactions in modulating activity of both dopaminergic and nondopaminergic neurons in VTA (Polter et al, ), quantification of KOR in VTA in humans would be of significant interest. However, VTA quantification is challenging with [ 11 C]GR103545 given the small volume of this structure and the low PET signal observed in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Given the role of dynorphin/KOR interactions in modulating activity of both dopaminergic and nondopaminergic neurons in VTA (Polter et al, ), quantification of KOR in VTA in humans would be of significant interest. However, VTA quantification is challenging with [ 11 C]GR103545 given the small volume of this structure and the low PET signal observed in this region.…”
Section: Discussionmentioning
confidence: 99%
“…It was speculated that this might improve an active coping and enhance a "flight or fight" response (Müller and Schumann, 2011a). Stress modifies the function of the mesolimbic DA system Kreibich et al, 2009) and its excitatory (Garcia-Keller et al, 2016) and inhibitory inputs (McLaughlin et al, 2003;Polter et al, 2017), in a way to cross-sensitize the system to subsequent psychostimulant behavioral effects and to their self-administration propensity (Cruz et al, 2011;. A single episode of social defeat stress can increase the mesocorticolimbic expression of the immediate early gene cFos, which is an indicator of neuronal activation Cooper et al, 2017).…”
Section: Facilitated Recovery and Coping With Psychological Stressmentioning
confidence: 99%
“…However, the same studies showed that days later an augmented effect emerges, which suggests that potential acute instrumentalization effects of the drug revert after a short time and render the organism in a drug-sensitized state that actually facilitates addiction-development . In the brain, µ-and -opioid receptor signaling and its activation by endogenous enkephalin and dynorphin, respectively, was enhanced after stress (McLaughlin et al, 2003;Nikulina et al, 2008;Polter et al, 2017).…”
Section: Facilitated Recovery and Coping With Psychological Stressmentioning
confidence: 99%
“…Additionally, stress is reported to augment addictive behaviors via an increase in the rewarding properties or rewarding memory of cocaine (McLaughlin et al, 2003;Kreibich et al, 2009;Schindler et al, 2010Schindler et al, , 2012Montagud-Romero et al, 2015). These modulations of addictive behaviors are attributed to stress-and aversive stimulus-induced neuroadaptation and the release of stress-related neurotransmitters and neuromodulators, such as corticotropin-releasing factor (CRF), the j-opioid agonist dynorphin, and noradrenaline (NA), in reward-related circuitry (Shaham & Hope, 2005;Smith & Aston-Jones, 2008;Ungless et al, 2010;Wise & Morales, 2010;Graziane et al, 2013;McReynolds et al, 2014;Polter & Kauer, 2014;Mantsch et al, 2016;Stelly et al, 2016;Polter et al, 2017). Moreover, studies have revealed that the effects of neurotransmitters and neuromodulators on information processing are altered following cocaine administration.…”
Section: Involvement Of Ldt Plasticity In Stress-related Behaviorsmentioning
confidence: 99%